GENDER DIFFERENCES IN VERBAL WORKING MEMORY - KONG, XIAN CHENG (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aimed to discover the gender differences in working memory among university students whose age and education level is similar. It is because there are inconsistent findings from the past studies such as some research found that female outperform male in verbal working memory task while some found there is no gender differences in performance related to verbal working memory. Besides, it is also found that there is not much research control other confounding variable such as age and education level which can also affect performance in working memory. Therefore, a quantitative research focus on the gender differences in verbal working memory is done with the control of age and education level. The instrument used is modified reading span task which sentences are extract from a course module familiar by the participants to ensure the language used is capable by all participants. Results shows that the differences in performance between male and female is not statistically significant. The results of this research showed that more similar studies are needed in order to discover gender differences in verbal working memory as the gender differences in verbal working memory does not shown in this research may be due to the low effect size of gender in verbal working memory performance.